PELAKSANAAN PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP OLEH DINAS LINGKUNGAN HIDUP KABUPATEN ROKAN HULU TERHADAP PETERNAKAN AYAM BROILER - Dio Josendra; M. Alpi Syahrin; Mus rifah (Yayasan Lembaga Pendidikan Asas, 2023)
The background to writing this thesis was that many chicken farming businesses in the Tandun District community were starting to feel disturbed due to pollution and environmental damage. Article 71 Paragraph (2) of Law Number 32 of 2009 concerning Environmental Protection and Management gives authority to the Rokan Hulu Environmental Service to protect and manage environmental conditions in its area. The problem in this thesis is how environmental protection and management is implemented by the Rokan Hulu Regency Environmental Service for broiler chicken farms in Tandun District, as well as factors that influence the implementation of environmental protection and management by the Rokan Hulu Regency Environmental Service for broiler chicken farms in the District. Tandan. The aim of this research is to determine the implementation and to determine the factors that influence environmental protection and management by the Rokan Hulu Regency Environmental Service for broiler chicken farming in Tandun District. The type of research that the author uses is sociological legal research where the researcher goes directly to the field. If you look at the nature of the research, this research is descriptive and uses a legal effectiveness approach, with data collection techniques in the form of observation, interviews, literature study and documentation. This research is located at the Rokan Hulu Regency Environmental Service. The results of the research show that the Rokan Hulu Regency Environmental Service in implementing environmental protection and management of broiler chicken farms in Tandun District has not run optimally. The influencing factors are that there has never been any outreach to livestock business actors, there has never been law enforcement or giving warnings and sanctions, and there is no supervision for chicken farming business actors. The inhibiting factors for the Rokan Hulu Regency Environmental Service are the lack of cooperation with business actors, the lack of human resources at the Rokan Hulu Environmental Service, and the lack of active community participation.